EFEKTIVITAS PEMBERIAN PARASETAMOL ORAL VERSUS PARASETAMOL REKTAL UNTUK ANTIPIRETIK PADA ANAK: SYSTEMATIC REVIEW - Sitta Hasanatin Sholihah (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT Paracetamol is available in oral and rectal formulations for decades. Controversies regarding conformity of formulations and dosages were found in the use of paracetamol as antipyretic. The purpose of this research is to know the effectiveness of paracetamol oral administration compared to the rectal administration for the loss of fever (antipyretic) in children that is systematic review. Research was done through searches from the database PubMed, NEJM, EBSCO, ProQuest, Science Direct. Systematic review was done on the child subject that aged 3 months to 13 years old and 1 month with fever and randomized trial with blind. Trials are examined based on predesigned inclusion criteria and exclusion criteria. Conducted systematic review and systematic review of randomized controlled trials was done to determine the effectiveness of the administration of paracetamol orally compared to the rectally. Data is homogeneous with RR 0.98 (CI 95%: 0.85-1.13). The effectiveness of the rectally compared to the oral administration of paracetamol is not significantly different in spite of the effectiveness of orally paracetamol amount of 0.98 times compared to the rectally. Keywords: antipyretic, child, orally paracetamol, rectally paracetamol